Self-adhesive, stretchable, and thermosensitive iontronic hydrogels for highly sensitive neuromorphic sensing−synaptic systems - Chen, Xuedan (2024)
Artificial sensory afferent nerves that emulate receptor nanochannel perception and synaptic ionic information processing in chemical environments are highly desirable for bioelectronics. However, challenges persist in achieving life-like nanoscale conformal contact, agile multimodal sensing response, and synaptic feedback with ions. Here, a precisely tuned phase transition poly(N-isopropylacrylamide) (PNIPAM) hydrogel is introduced through the water molecule reservoir strategy. The resulting hydrogel with strongly cross-linked networks exhibits excellent mechanical performance (∼2000% elongation) and robust adhesive strength. Importantly, the hydrogel's enhanced ionic conductance and heterogeneous structure of the temperature-sensitive component enable highly sensitive strain information perception (GFmax = 7.94, response time ∼ 87 ms), temperature information perception (TCRmax = -1.974%/°C, response time ∼ 270 ms), and low energy consumption synaptic plasticity (42.2 fJ/spike). As a demonstration, a neuromorphic sensing-synaptic system is constructed integrating iontronic strain/temperature sensors with fiber synapses for real-time information sensing, discrimination, and feedback. This work holds enormous potential in bioinspired robotics and bioelectronics.